2008
DOI: 10.1509/jmkg.72.5.131
|View full text |Cite
|
Sign up to set email alerts
|

How Customer Portfolio Affects New Product Development in Technology-Based Entrepreneurial Firms

Abstract: This article focuses on how the customer portfolios of technology-based entrepreneurial firms affect new product development. Drawing on knowledge-based, resource dependence, and relational theories, the authors argue that the impact of a firm's customers on new product development depends on the size and relational embeddedness of the customer portfolio and the extent to which the firm is dependent on one or a few dominant customers for a majority of its revenues. The authors test the research model using lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(113 citation statements)
references
References 118 publications
6
107
0
Order By: Relevance
“…This fi nding contributes not only to the internationalization literature but also to the broader interorganizational relationship literature by extending the focus from formal alliances, joint ventures, and acquisitions to a fi rm's broader set of exchange relationships and by extending the set of outcomes that have been studied. Previous studies have found that knowledge transfer and spillovers between exchange partners can benefi t, for example, new product development (Deeds and Hill, 1996;Yli-Renko and Janakiraman, 2008), marketing skill development (Simonin, 1999), and sales cost effi ciency (Yli-Renko et al, 2001). Our fi ndings indicate that such learning effects also hold when the focal outcome is the extent of internationalization.…”
supporting
confidence: 60%
“…This fi nding contributes not only to the internationalization literature but also to the broader interorganizational relationship literature by extending the focus from formal alliances, joint ventures, and acquisitions to a fi rm's broader set of exchange relationships and by extending the set of outcomes that have been studied. Previous studies have found that knowledge transfer and spillovers between exchange partners can benefi t, for example, new product development (Deeds and Hill, 1996;Yli-Renko and Janakiraman, 2008), marketing skill development (Simonin, 1999), and sales cost effi ciency (Yli-Renko et al, 2001). Our fi ndings indicate that such learning effects also hold when the focal outcome is the extent of internationalization.…”
supporting
confidence: 60%
“…Furthermore, it has been argued that, instead of focusing on pushing the technology to the market, entrepreneurs gain more from getting knowledge from key customers and then tailoring their new products and services to their emerging needs (Yli-Renko & Janakiraman, 2008).…”
Section: Technology and The Entrepreneurship Processmentioning
confidence: 99%
“…One of the advantages of a partnership between an SME and a large corporation would be the access to financial capital or to the global market (Alvarez et al, 2006). In addition, a large portfolio allows exposition to a wider resource basis, thus providing expertise in the effects of scale on the organization's development and growth (Yli-Renko & Janakiraman, 2008). …”
Section: Strategic Alliancesmentioning
confidence: 99%
“…Another kind of partnership that can bring benefits to a small or new company is the maintenance of a strong, close relationship with its clients (Yli-Renko & Janakiraman, 2008). Alliances can represent both risks and opportunities, particularly for SMEs with limited resources.…”
Section: Strategic Alliancesmentioning
confidence: 99%